Definition and influencing factors of difficulty hospital discharge using focus group. - Akkayagorn, L.; Chatrkaw, P.; Sriratanabal , P.; Manasvanich , B.; Sa-nguansap , T.; Meethavorn, N.; Udayachalem , C. (Chulalongkorn Medical Journal, 2023)
Background : In university hospitals and tertiary level hospitals, which have complexities, the patients and the medical teams are frequently faced with difficult situations in leaving or discharging patients from the hospital, thereby resulting in prolonged hospital stay. Objectives : For a better understanding of “Difficult Hospital Discharge” (DHD), this study is aimed to determine the definition of DHD and to identify common influencing factors from the view points of medical staff as well as the definition of “prolonged hospital stay” (PHS). Methods : Four focus-group interviews for total 37 experienced multi-disciplinary participants were performed intensively by a well-trained interviewer. The data obtained from the groups were analyzed and then conveyed into working definitions for DHD and PHS. Potential associating factors mentioned in the groups were also collected and classified. Results : The definition of PHS was defined as a situation when a patient has occupied a bed in a tertiary care hospital longer than the system anticipates or recognized by any of the following criteria: 1) Thai diagnosis related groups (DRGs): 2) Average occupying days of each ward: 3) Average medical expense of each diagnoses: or 4) Inability to discharge despite the existing discharge order. Meaningfully, the last criteria of PHS was found to be the definition of DHD when it came together with a feeling of difficulty resulted from discharge order in the patient, the family or the medical team. The 3 most quoted factors that might promote DHD were: 1) Burden from excessive care expense 2) Fear of clinical instability after leaving a hospital and 3) Unfeasible residences or housings. The 3 most quoted factors anticipated to prevent DHD were: 1) Standard programs to acknowledge caregivers on how to care the patient at home 2) Holistic discharge planning initiated a head of discharge time and 3) Proper palliative care introduction and education. Conclusion : This study gives practical definitions of PHS and DHD as well as positively and negatively influencing factors. The data could be used as a base for further research and hospital management.